Analisis Unsur Permulaan Pelaksanaan Dalam Tindak Pidana Makar - Febby Farizky Siregar; Alvi Syahrin; M Ekaputra (Iuris Studia: Jurnal Kajian Hukum, 2021)
As a condition for the crime of treason, the initial element of implementation is something that greatly influences whether or not a person can be charged with the crime of treason. A person can be said to have committed a crime of treason; it must first be proven regarding the intention of the perpetrator stated at the beginning of the implementation which is one of the elements of an attempt to commit a crime One example is the case of treason in Decision Number 1303/Pid.B/2019/PN.Jkt.Pst..Based on the background description, the problems studied are: How is the regulation of the crime of treason in Indonesia, how is the relationship between the beginning of the implementation and the crime of treason, how is the legal analysis of the crime of treason in Decision Number: 1303/PID.B/2019/PN. JKT.PST.The research method used in this research is normative legal research, which is supported by secondary data sources, and qualitative analysis is carried out.The result of the research is that the regulation of the crime of treason in Indonesia is regulated in several articles, including Article 104, Article 106 of the Criminal Code and Article 107 of the Criminal Code. The link between the initial element of implementation and the element of the criminal act of treason in essence has an interrelated relationship, as can be seen in Article 87 of the Criminal Code, so that the crime of treason can be said to have occurred, if the initial element in the form of the perpetrator's intention has been proven as the initial act in committing the crime. treason. Legal analysis is related to the decision of the Central Jakarta District Court Number 1303/Pid.B/2019/PN Jkt.Pst, the perpetrator's actions should not be subject to Article 106 of the Criminal Code Jo. Article 55 of the Criminal Code, but should be subject to Article 106 Jo. Article 87 of the Criminal Code concerning the act of treason is coupled with the attempted treason itself, so that it can be said that the fundamental error lies in the prosecutor's error in prosecuting the actions of the defendants, so the legal analysis states that the prosecutor's demands in this case are what make the application of the law imposed incompatible with panel of judges.